Surgical Experience of Transcranial Approaches to Large-to-Giant Pituitary Adenomas in Knosp Grade 4 - Guan, Xiudong; Wang, Yangyang; Zhang, Chengkai; Ma, Shunchang; Zhou, Wenjianlong; Jia, Guijun; Jia, Wang (Frontiers in Endocrinology, 2022)
Pituitary adenomas in Knosp grade 4 are difficult to resect completely and are generally involved in poor prognosis, because of the close relationship between the tumor and internal carotid. In this study, the authors retrospectively reviewed the outcome of different transcranial approaches in the management of large-to-giant pituitary adenomas in Knosp grade 4. A total of 42 patients with large-to-giant pituitary adenomas in Knosp grade 4, who underwent craniotomy in the Pituitary Disease Subdivision, Department of Neurosurgery, Beijing Tiantan Hospital, between March 2012 and March 2015 were included in this study. Clinical characteristics, surgical methods, complications, and outcomes were evaluated. The median age was 45 years (range, 19–73 years old), and 42.9% of the enrolled cases were men. The mean tumor diameter was 43.6 mm, and the mean volume was 30.9 cm3. 26 patients underwent the frontolateral approach, while 16 cases accepted the frontotemporal approach. Gross total resection was achieved in 11 patients (26.2%), near total in 26 (61.9%), and subtotal in 5 (11.9%). The adenomas were larger, and the distance of the tumor extending to the lateral skull base was also further in the frontotemporal approach cases. The surgical time was shorter, and the bleeding volume was less in the frontolateral approach cases. Subsellar extension was associated with incomplete resection in pituitary macroadenomas of Knosp grade 4. The craniotomy is still an effective treatment for pituitary macroadenomas in Knosp grade 4.